2017
DOI: 10.4306/jknpa.2017.56.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Korean version of Richmond Compulsive Buying Scale

Abstract: ObjectivesZZThe purpose of this study was to evaluate the psychometric properties of the Korean version of the Richmond Compulsive Buying Scale (RCB-K).MethodsZZParticipants (n=598) included patients recruited through an online panel survey. For the semantic adaptation step, the scale was translated into Korean and then back-translated to English by one psychologist, one public health professional, one psychiatrist who could speak both Korean and English, and one professional translator, without communication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The results of this study contribute to the findings of extant literature on the applicability of RCBS in various cultural and national groups ( Byeon et al., 2017 ; Horváth et al., 2013 ; Leite et al., 2013 ; Maraz et al., 2015 ; Ridgway et al., 2008 ). RCBS and RCBS-TC are useful epidemiological instruments for examining the prevalence of CBB.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The results of this study contribute to the findings of extant literature on the applicability of RCBS in various cultural and national groups ( Byeon et al., 2017 ; Horváth et al., 2013 ; Leite et al., 2013 ; Maraz et al., 2015 ; Ridgway et al., 2008 ). RCBS and RCBS-TC are useful epidemiological instruments for examining the prevalence of CBB.…”
Section: Discussionsupporting
confidence: 60%
“…The cut-off validity was confirmed using the actual purchase data of online shoppers. Since then, RCBS has been translated to five (or more) languages and has been validated in both developed and developing countries ( Byeon et al., 2017 ; He, Kukar-Kinney, & Ridgway, 2018 ; Horváth, van Herk, & Adigüzel, 2013 ; Leite et al., 2013 ; Maraz et al., 2015 ).…”
Section: Compulsive Buyingmentioning
confidence: 99%
“…Investigators classified the participants into two groups (i.e., PIS and NPIS) based on their RCBS score. Byeon et al [48] suggested that a score of 25 points or higher on the Korean version of the RCBS indicates a problematic shopper. We classified those whose RCBS score was 25 or more as the PIS group.…”
Section: Discussionmentioning
confidence: 99%
“…Attention-Deficit Hyperactivity Disorder Rating Scale (ADHD-RS) is 18-item questionnaire completed by the teacher or the parent to help diagnose ADHD. In this study, we used the well-validated Korean version of ADHD-RS administered by parents (So et al, 2002). There are 9 items reflecting symptoms of inattention and 9 items reflecting symptoms of hyperactivity and impulsivity.…”
Section: Methodsmentioning
confidence: 99%